Os sentidos atribuídos por professoras de 2º ano do ensino fundamental às práticas docentes de alfabetização de alunos com deficiência intelectual - Costa, Francisca Mônica Silva da (2021)
The research aims at analyzing the meanings attributed to the literacy teaching practices by 2nd-year-elementary-school teachers. They teach students with some intellectual disabilities enrolled in regular classes. The theoretical background is supported by the cultural-historical perspective; especially, on the studies of Vygotsky and Luria. Qualitative collaborative research was adopted and five 2nd-year-elementary-school teachers (TA, TB, TC, TD, and TE) from a municipal school in Fortaleza took part in it. They had students with some intellectual disabilities enrolled in their classes. The construction of data was developed throughout collaborative meetings, reflective sessions, the application of individual and group interviews, collaborative observations, document analysis and follow-up assessments of the literacy process of students with some intellectual disabilities. The analysis was carried out based on the assumptions of Fairclough's Critical Discourse Analysis. The results suggested, at the beginning of the research, that three teachers (TB, TC, and TD) attributed meanings related to the standard teaching practice and two of them (TA and TE) to those practices focusing on differences. Later, they started to assume a teaching practice nominated, in this study, as dialectic. The three teachers whose practice were predominantly standardized developed a perspective anchored in a transmissive and uniform teaching approach. There was a greater tendency to privilege the biologizing view of intellectual disability in their speeches. The obstacles faced during the literacy process were only explained as factors inherent to the biological condition, which, in turn, shows low expectations regarding the learning capacity of these students. The other two teachers taught more openly; they accounted different learning possibilities and did not ignore the peculiarities of the knowledge construction process of the students. It was also found that they considered affective aspects, social interaction, collaborative work, and mediation during teaching. All these aspects have as features the attention to the educational needs of all students, the understanding that learning can occur in different ways and the belief in the possibilities of learning regardless of a diagnosis. Furthermore, it was noticed, through the process of critical reflection that took place in the training experiences carried out in a collaborative context, that the meanings attributed to the literacy teaching practices for students with intellectual disabilities were negotiated and modified. That posture changes their classes, which resulted in the development of a teaching practice designated as dialectics. The meanings regarding their practice were characterized by constant critical reflection; the understanding that each student needs to be recognized as the author of their constructions; and that the learning possibilities of these students are directly related to the teaching opportunities that are provided to them. The changing process implemented is complex, dynamic, and takes into consideration the subjectivity of each one of the participants; hence, it is presented differently in each one of them. It is concluded that, although professional development occurs at different times for each of the teachers, collaborative training favored the expansion of the level of awareness about the literacy practice of them and the resignification of the meanings credited to it